Financial Ratio Analysis to Predict Financial Distress at PT. Perkebunan Nusantara IV (Persero) Medan - Febri Bahri; Rahima Br. Purba; Oktarini Khamilah (Britain International for Academic Research (BIAR-Publisher), 2022)
This study is entitled